Imaginação material e mística: traços dos quatro elementos naturais presentes na obra Castelo Interior de Santa Teresa d’Ávila - Prates, Admilson Eustáquio (2016)
The research focuses on a classic work of Spanish Christianity of the Sixteenth Century, whose purpose is to study the Material and Mystical Imagination: traces of the four natural elements present in the work Interior Castle of St. Teresa d'Ávila. The object of research is composed of two aspects, one material or general and other formal or specific. The material aspect is the work Interior Castle of St. Teresa of Jesus. The formal aspect of the object is to identify traces of the four symbolic natural elements present in the mystical narrative. For that, we turn to the theoretical Gaston Bachelard in order to identify the four natural elements in the work. The ways, methodological procedures, which intended to follow to the resolution of the problem of this research are theoretical. In the theoretical field, will be developed a literature search (presented the authors / researchers in justification and bibliography) that approximates the question of religiosity, spirituality and mystic with the question of culture. First, we will do an approximatively reading to familiarize with the text, from the lens of the four natural elements, that is, imagination material in Gaston Bachelard. Then we will perform the collection of the Castle Interior work passages that indicate the presence of the four natural elements, that is, the material imagination. Thus, will be held the book report of the work and explored the passages according to the prospect of symbolic hermeneutics based on Gaston Bachelard. The third, final step in this process, is to apply the interpretation methodology, that is, the symbolic hermeneutic. That way, we will use for this research the symbolic hermeneutics in the work Interior Castle, from studies about material imagination in Gaston Bachelard